-5n-8(1+7n)=-8

- 5n - 8(1 + 7n) = - 8

Now multiply -8 in the bracket which will change the signs of the term inside, then

- 5n - 8 - 56n = - 8

Now

- 5n - 56n - 8 = - 8

- 61n - 8 = -8

Now add 8 on both sides, we get

- 61n - 8 + 8 = - 8 + 8

- 61n = 0

Now divide by -61 on both sides, we get

- 61n / -61 = 0/-61

n = 0

Hence n = 0

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up